PERJALANAN HIDUP CARL LINNAEUS SEORANG DOKTER BANGSA SWEDIA YANG MENJADI PAKAR BOTANI DAN ZOOLOGIKALIBER DUNIA - S Somadikarta (Research Center for Biology-Indonesian Institute of Sciences, 2007)
A baby boy was born in Rashult, Smoland, Sweden, on 23 May 1707, who later became the world famous Swedish botanist and deservedly be called The World's Father of Taxonomy. The baby was baptized as Carl Linnaeus. According to Swedish customs at that time, the baby should had been named Carl Nilsson (Carl, son of Nils), since his father's name was Nils Ingemarsson (Nils,son of Ingemar Bengtson).When Nils Ingemarsson was enrolling the University of Lund, he had - based on the university rules- to have a family name. He choosed Linnaeus as his family name, and since then Nils Ingermarsson was known as Nils Linnaeus.Carl Linnaeus (hereafter Linnaeus) finished his primary school and Gymansium at Vaxyo. After graduation from the Gymnasium,Linnaeus was trained as dress- and shoemaker before pursuing medical studies at the University of Lund in 1727.A year later he moved to the University of Uppsala. Linnaeus got his medical doctorate from the University of Harderwijk (Holland) on 23 June 1735. Before returning to Sweden, Linnaeus was working and visiting several places. He had the opportunity to meet many outstanding botanists during his visits. When he was working (1735-1737) at